Case report: Ramsay Hunt Syndrome - Borges, Mariana Queiroz (2022)
The aim of this study is to report a case of a woman with Ramsay Hunt Syndrome (SRH). Female patient, 39 years old, presenting a vascular lesion in direct external auditory pavilhão, ipsilateral peripheral facial paralysis, later presenting a partial hearing loss in audiometry, presenting a classic quadro case of SRH. Amongst the laboratory tests, reagent sorology for Herpes Simplex type I and II, reagent IgG and Varicose Zoster, IgM and IgG reagents. Either the treatment used was acyclovir, tenofovir and predinisone, or that produced a partial melt of peripheral facial paralysis associated with or disappearance of injuries. The chart presented demonstrates the importance of an early diagnosis and treatment without a correct period and is essential for a good prognosis, avoiding the possible presence of mutilating motor nerve sequelae.